Determinants of value and challenges of older persons in Uganda - Nzabona, Abel. (Kampala, 2015)
Unpublished thesis (PHD) - Makerere University, 2015.
Includes bibliographical references.
Keywords: Older people -- Economic conditions; Older people -- Social conditions